No Association between Estrogen Receptor-Β Rs4986938 and Cancer Risk: A Systematic Review and Meta-Analysis - Zhaofang LI; Xiaoli YANG; Rongqiang ZHANG; Baorong LI; Di ZHANG; Qiang LI; Yongmin XIONG (Tehran University of Medical Sciences, 2019)
Background: The association between estrogen receptor-β (ESR2) rs4986938 polymorphism and the risk of various types of cancer have been investigated in previous studies. However, the results remained disputable. Here, we conducted a meta-analysis to investigate the association between ESR2 rs4986938 polymorphism and the risk of cancer. Methods: We searched for relevant articles collected by the PubMed, EMBASE, and Cochrane library up to March 30, 2018. The association was assessed using Odds ratios (ORs) and 95% confidence intervals (CIs). Results: The meta-analysis involved a total of 23 studies in 20 papers, including 24,334 cases and 31,707 controls. No significant association was detected between the rs4986938 polymorphism and cancer risk in the additive model (A compared with G: OR=0.97, 95% CI=0.92-1.02, P=0.20), dominant model (AA+AG compared with GG: OR=0.96, 95% CI=0.93-1.03, P=1.00), recessive model (AA compared with AG + GG: OR=0.94, 95% CI=0.86-1.03, P=0.18), heterozygous model (AG compared with GG: OR=0.97, 95% CI=0.94-1.01, P=0.14), and homozygous model (AA compared with GG: OR=0.96, 95% CI=0.87-1.06, P=0.39). Results of subgroup analysis stratified by ethnicity and cancer types further validated the results. Conclusion: We found no evidence of an association between rs4986938 and the risk of overall cancer.